Experiencing (Pereživanie) as Developmental Category: Learning from a Fisherman who is Becoming (as) a Teacher-in-a-Village-School - Jóhannsdóttir, Thurídur; Roth, Wollf-Michael (Outlines. Critical Practice Studies, 2014)
In this study, we take up L. S. Vygotsky’s challenge to study learning and development in terms of categories, irreducible units that preserve the characteristics of the whole (society). One such category (unit) is experiencing [pereživanie], a process that integrates over the relation of person and environment. Using a case study from Iceland, we theorize the process of “becoming as a teacher-in-a-village school” in terms of experiencing [pereživanie]. The case describes a stage of development in the life of a person who becomes a teacher and then experiences a developmental trajectory very different from his previous life as a fisherman. This is an aspect of teacher education that is hardly (if ever) described in the teacher education literature which tend to be concerned with events after a person has entered a professional program or after a person has begun teaching. We discuss the implications of taking experiencing [pereživanie] as the developmental unit for theory and the practice of teacher education and development.